Coach and no regrets about it: On the life satisfaction, work-related mental strain, and use of supervision of workplace coaches. Issue 1 (2nd January 2020) - Müller, Alessa A.; Kotte, Silja; Möller, Heidi
ABSTRACT: Previous research indicates that coaches frequently experience negative effects for themselves from their work and therefore live with potential stressors due to their work. This study examines whether or not workplace coaches are satisfied with their life. Data were gathered from 110 coaches (75% of which were self-employed) from Germany, Austria, and Switzerland via an online survey. Coaches were asked about different aspects of life satisfaction (concerning their job, financial situation, and leisure time) and work-related mental strain (i.e., cognitive and emotional strain). Compared to German population norm scores (including both employed and self-employed working individuals), coaches show higher satisfaction with their job and leisure time, and less work-related mental strain. Moreover, the vast majority of coaches would choose to be a workplace coach again in retrospect. Coaching supervision had a significant buffer effect on coaches' job satisfaction when they experienced a high amount of work-related mental strain. Findings imply that coaches are able to counterbalance the possible negative effects on life satisfaction of their work as coaches. The use of coaching supervision appears to be a successful measure to maintain high satisfaction with their work as coaches despite an elevated level of mental strain.